Tai magic arts of the supernatural in the Shan states and Lan Na - Conway, Susan (River Books, 2014)
"Introduces manuscripts, textiles and talismans associated with the supernatural. Within the context of Tai cosmology and numerology, Theravada Buddhism and spirit religion, the book examines how good and bad spirits are represented in figurative illustrations and how mystical diagrams and spells are formulated to bring good luck and protection or cause bad luck."--Jacket.